IMF and the Baltics : A Decade of Cooperation - Knobl, Adalbert (IMF Working Papers; Working Paper ;, 2003)
The paper is an economic history of the IMF's involvement in the Baltic states. It describes and analyzes the initial economic stabilization; the period of consolidation and recovery; the effects of the Russian crisis of 1998; and the current growth phases of Lithuania, Latvia, and Estonia. There is also an assessment of cooperation with the Fund based on interviews with a number of ex-officials. The major conclusion is that the Baltics have been so successful because of their early commitment to change the stabilization and reform policies needed for successful transition, and their ownership of their IMF-supported programs.